HUBUNGAN ANTARA KELINCAHAN DAN KECEPATAN TERHADAP KEMAMPUAN MENDRIBEL BOLA PEMAIN PS. MESKOM KECAMATAN BENGKALIS - Herman Sutrisno; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study originated from the observation of the author encountered in the field, that footballers PS. Meskom District of Bengkalis can not dribble the ball well when playing football. This is presumably due to a lack of agility and speed which is owned by the player PS. Meskom District of Bengkalis. The purpose of this study was to determine the relationship of the agility and speed of the ball on the player's ability to dribble the PS. Meskom District of Bengkalis. This type of research is correlational. The population in this study are players PS. Meskom District of Bengkalis, amounting to 62 people consisting of three (3) age group, sampling in this research is using purposive sampling technique namely the U.17 - U.22 year, which amounted to as many as 20 people. to obtain research data used zig-zag run, the test run 30 meters and the ability to dribble the ball. Data were analyzed with simple product moment correlation and multiple, Based on data analysis found that there is a significant relationship between agility on the ability to dribble the ball, which rtab at significant level α (0,05) = 0.444 means rhitung (0,482)> rtab (0.444 ). Then at speed with the ability to dribble the ball also a significant relationship, where rtab at significant level α (0,05) = 0.444 means rhitung (0.500)> rtab (0.444). And then there is also a significant relationship jointly between agility and speed of the ball on the player's ability to dribble the PS. Meskom District of Bengkalis, where rtab at significant level α (0,05) = 0.444 means rhitung (0.555)> rtab (0.444).Keywords : Agility, Speed, Ability of Dribbling